Clinical features of childhood narcolepsy. Can cataplexy be foretold? - Nevsimalova, Sona; Jara, Cecilia; Prihodova, Iva; Kemlink, David; Sonka, Karel; Skibova, Jelena (European journal of paediatric neurology, 2011)
BACKGROUND: Narcolepsy is a life-long disease characterized by abnormal regulation of the sleep-wake cycle and increased penetration of rapid eye movement (REM) sleep. In children, narcolepsy without cataplexy is more frequently seen than in adults. The aim of our study was to evaluate clinical and polysomnographic parameters to verify if cataplexy appearing later in life can be foretold. METHODS: 30 patients (12 boys), who contracted narcolepsy before the age of 18, were enrolled. All underwent clinical examination, nocturnal polysomnography (PSG), multiple sleep latency test (MSLT), HLA-DQB1∗0602 testing and, most of them Epworth Sleepiness Scale (ESS) rating. The Mann-Whitney rank and Fisher's tests were used for statistical analysis. RESULTS: Narcolepsy without cataplexy (NwC) was diagnosed in 40% of the patients. The mean age at the first symptoms was 14.0 ± 3.0, at diagnosis 15.6 ± 3.1 years. Narcolepsy was accompanied by hypnagogic hallucinations in 15 and sleep paralysis in 12 patients. Frequent symptoms were sleep inertia during awakening, REM behavior symptoms, behavioral and serious school problems. BMI was higher in patients with narcolepsy-cataplexy (N-C). A high ESS score was indicative of excessive daytime sleepiness (17.1 ± 2.5). Mean MSLT sleep latency was 4.0 ± 3.1 min with 3.2 ± 1.4 sleep onset REM periods (SOREMs) with no difference between the two study groups. HLA typing revealed no differences either. The N-C group showed a higher degree of wakefulness and superficial non-REM (NREM) stage 1 with a lower NREM stage 3 during PSG. CONCLUSION: Narcolepsy in childhood leaves very little scope for the prediction of cataplexy later in life.
Keywords: Humans; Hallucinations; dítě; kohortové studie; Predictive Value of Tests; Child; polysomnografie; Female; Narcolepsy; bdění; Polysomnography; halucinace; REM Sleep Parasomnias; lidé; narkolepsie; spánek REM; parasomnie spojené s REM spánkem; Cohort Studies; ženské pohlaví; Male; prediktivní hodnota testů; Wakefulness; Adolescent; prognóza; Sleep, REM; věk při počátku nemoci; mužské pohlaví; Age of Onset; Prognosis; mladiství